Estudos comparativos de três diferentes scaffolds pra crescimento de célula tronco mesenquimal, fibroblastos e queratinócitos - Nunes, Helga Caputo [UNESP] (2014)
Introduction: Tissue engineering comprises in organ and proper tissue regeneration achieved by collecting small tissue fragments that are dissociated into cells and then cultivated into biological or synthetics scaffolds. The main characteristic of these constructs is their capacity to behave as their biological matrix counterparts, providing mechanical support and the required micro environment to the cells. This technology paves the way for the creation of functional and vital tissues for transplants. Within Biomedical Engineering and Biomaterials, the Cell Engineering Laboratory of the Botucatu Blood Transfusion Center has been investigating these topics since 2001, starting with the production of biological dressings. Biological dressings interact actively with the several phases of chronic wounds, which involves high economic, social and psychological costs, often condemning the patients quality of life. Considering this reality, the contribution of tissue engineering is to develop alternatives on cell therapy using scaffold technology. Aims: To assess the performance of different biological scaffolds such as fibrin glue, platelet gel and chitosan membrane for cell culture. Material and Methods: Five fragments of adipose tissue and skin were collected, dissociate with mechanical, enzymatic and explant techniques, and the resulting cells were seeded on tissue culture flasks, amplified and characterized using multiparameter techniques. Following characterization, these cells were cultivated into three different scaffolds made of fibrin glue, platelet gel and chitosan - which was performed in two distinct ways, on its natural form and incorporated with platelet-derived growth factors to analyze this interaction. Discussion and Results: cell cultures were amplified and cultivated making a good cell bank. However, keratinocytes were difficult to grow and the rest of experiments were unfeasible to drawn up. Immunocytochemistry analysis ...